Legal mechanisms of public authority implementation in the de-occupied territories of Ukraine - Klimova, Svitlana (Theory and Practice of Public Administration, 2026)
The article provides a comprehensive study of the legal mechanisms for implementing public authority in the de-occupied territories of Ukraine from institutional, organizational, legal, and financial perspectives. It is substantiated that the restoration of public authority in territories temporarily occupied as a result of the armed aggression of the Russian Federation is a key prerequisite for ensuring state sovereignty, territorial integrity, the rule of law, and the sustainable development of territorial communities. The institutional and legal mechanisms of exercising state power in de-occupied territories are analyzed. It is established that the Verkhovna Rada of Ukraine, the President of Ukraine, the Cabinet of Ministers of Ukraine, and central executive authorities play a leading role in the reintegration process by forming the legal framework for recovery, ensuring security, implementing reconstruction policies, and coordinating public administration activities. It is proven that the effectiveness of these institutions depends on proper legal regulation, interagency cooperation, and compliance with the principles of good governance. The organizational and legal foundations of territorial-level public authority are examined. Particular attention is paid to the activities of local state administrations, military administrations, and local self-government bodies during the de-occupation process. It is demonstrated that restoring institutional capacity, professional staffing, access to administrative services, public security, and administrative justice is a necessary condition for the successful reintegration of de-occupied territories and rebuilding public trust in state institutions. The financial and legal mechanisms supporting public authorities in de-occupied territories are studied. It is established that budgetary instruments, state target programs, regional development policy mechanisms, public investments, public-private partnerships, and international financial assistance constitute the main sources of recovery financing. The need to strengthen transparency, accountability, and efficiency in the use of public financial resources through improved state financial control and anti-corruption mechanisms is substantiated. Based on the research conducted, proposals are formulated to improve the legal framework for public authorities in de-occupied territories by introducing a special legal regime for a ten-year transitional period following de-occupation. The expediency of establishing a specific legal status for public authorities operating in such territories is substantiated. It is proposed to grant these authorities the right of legislative initiative on recovery and development issues, as well as enhanced powers to independently manage financial resources under the permanent supervision of state financial control bodies. The study also substantiates granting these authorities the power to enter into agreements with international financial organizations for reconstruction and development projects. Furthermore, special tax regimes for investors participating in the reconstruction of occupied territories are proposed to stimulate investment, accelerate economic recovery, and ensure sustainable community development.